It must be my metabolism! a doctor's proven program for losing weight by reversing metabolic syndrome - Yavari, Reza (McGraw Hill, 2006)
"A collection of seemingly unrelated medical disorders, metabolic syndrome includes heart disease, excess abdominal fat, sleep problems, infertility, insulin resistance and full-fledged diabetes. When combined, these disorders pose a serious health risk that doctors and consumers are increasingly aware of. It must be my metabolism! shows readers, step-by-step, how to make the changes necessary to lose the "apple" shape that so often comes at midlife, and regain both a youthful figure and better health"